Explication of Nature in Śrī Kṛṣṇa Līlā in the Śrimad Bhāgavata Mahāpurāṇa - Pokhrel, Mohan Kumar (JODEM: Journal of Language and Literature, 2023)
This article explores Nature in Śrī Kṛṣṇa līlā (Divine Play) as manifested in the Śrimad Bhāgavata Mahāpurāṇa. Within its verses, the text weaves a tapestry where Nature serves as an integral backdrop, metaphor, and source of inspiration for the divine narrative. The epic incorporates discussion on various aspects of Nature which in the Bhāgavata is deeply connected with the playful activities of Śrī Kṛṣṇa. The major objectives of this study are to explicate relation between Śrī Kṛṣṇa līlā and Nature as reflected in the Bhāgavata; to explore linkages between Śrī Kṛṣṇa līlā and Nature, and to evaluate Śrī Kṛṣṇa līlā on the basis of Nature. For the analysis of the primary text, the researcher has used Baruch Spinoza’s principle on Nature. The theorist claims divine beings in the objects of Nature and argues when the law of Nature ends, tyranny begins. The researcher has used interpretative method for the exploration of Nature in Śrī Kṛṣṇa līlā. This study is innovative because it encourages humans to dedicate their lives for the conservation of Nature. The results of examining Śrī Kṛṣṇa līlā and Nature in the Bhāgavata highlight the sanctity of Nature, the interconnectedness of all beings, the potential for transcendence through Nature, the symbolism inherent in natural elements, and moral lessons derived from Śrī Kṛṣṇa’s interaction with Nature. The prime conclusion drawn from this research is that Nature serves as the setting and the teacher in the playful activities of Śrī Kṛṣṇa. It encourages humans to develop positive attitude of love, devotion, and service towards the divinity and the natural world.